A frequency study of rainfall for the Periyar basin of Kerala (MAUSAM, 1988)
A rainfall depth-duration-frequency study was carried out for the Periyar river basin of Kerala using average sixty years of data from fourteen raingauge stations distributed in an area of 5398 km'. The annual maximum rainfall depths of 1, 2, 3, 7 and 10 days durations were analysed. The extreme value Type-1 distribution fitted with maximum likelihood estimates. was utilized to .derive the re9uired relationships. Analyses were carried out for the Individual stations and later regional relationships were obtained based on the station-year concept. The regions were demarcated considering rainfall and topographical characteristics. Satisfactory results were obtained. The results obtained from the regional study are expected to be useful for design engineers and agricultural scientists.